Driver’s reaction time in a simulated, complex road incident - Jurecki, Rafał S.; Stańczyk, Tomasz L.; Jaśkiewicz, Marek J. (Transport, 2017)
This paper presents an overview of research on the behaviour of drivers in simulated accident situations. The research was carried out by the authors of this work as a part of a research N N509 549 040 funded by the National Science Centre including new accident situations. The paper presents a description of the methodology and implementation of research on a track. During the tests, the simulation concerns about an accident risk situation involving pedestrians and passenger cars intruding the road area. In contrast to earlier research carried out by the authors, the scenario included the possibility of a pedestrian ‘entering’ from behind a curtain, both from the left and from the right sides of the road. This was possible thanks to a specially developed test stand. The paper analyses the values of driver’s reaction times characteristic to driver’s impact on: acceleration control pedals, service brake and steering wheel. In addition to the determination of average reaction time values and the regression line for the test group of 30 drivers, the assessment of the frequency of drivers taking individual defensive reactions was carried out. Keywords: traffic safety; collision; road accidents; regression equation; simulation.First published online: 09 May 2014